Are all Mexican odonate species documented? An assessment of species richness. Issue 3 (4th May 2017) - Cuevas–Yañez, K.; Espinosa–Rivera, J. C.; Martínez–Falcón, A. P.; Córdoba–Aguilar, Alex
Abstract : With the aim of protecting Mexican diversity, one current governmental task is to complete national biological inventories. In the case of odonate insects, several researchers have hypothesized that species richness is complete (205 dragonflies and 151 damselflies), but there has not been any formal exercise to test this. Thus, we have investigated whether odonate species richness (for Mexican endemics, dragonflies (suborder Anisoptera), damselflies (suborder Zygoptera) and total species) is complete using sample-based and coverage-based rarefaction curves. Along with this, we also showed how good distribution data are in the country. The rarefaction curves have indicated 100% completeness for all groups suggesting that the inventory is complete. However, species' distribution data is highly patchy regarding areas either well (e.g. central Mexico) or badly (e.g. coast of Guerrero and Oaxaca) collected. We encourage researchers to continue odonate sampling in order to support at least three conservation actions: (i) conservation assessment of endangered species; (ii) knowledge of range shifts given rising global temperatures; and (iii) increase public interest and awareness in protected, touristic areas.